Effects of ladle lid or online preheating on heat preservation of ladle linings and temperature drop of molten steel. (1st January 2021) - Zhang, Huining; Zhou, Peiling; Yuan, Fei
Abstract: Two usual ways used in steel plants to preserve the heat of the ladle lining are online preheating and ladle capping. In this study, the finite volume method (FVM) was adopted to build a combustion and fluid-solid heat transfer 3D model for online preheating, and a fluid-solid heat transfer 3D model for the process of ladle capping and the heavy ladle. The numerical computational analysis was conducted by the Fluent software. Through the weighted sum of grey gases model (WSGGM), variable emissivity and absorptivity of the flue gas during the preheating process were taken into account and added into the energy conservation equation of the flue gas in the form of a source item via the radiation transfer equation. This paper analyzed the influence of the two heat-preserving measures, namely ladle capping and online preheating by means of regenerative combustion, on the heat preservation effect of the ladle lining, and further compared and analyzed their effects on the temperature drop of molten steel. As suggested by the results, capping during the empty ladle process had better effect on the molten steel's temperature drop than during the heavy ladle process. Full-process capping can reduce the molten steel's temperature drop rate by 0.11 K min −1 than when no capping was added at all. When 10–30 min of online preheating was applied during empty ladle process, the average temperature of the working lining of the ladle can be raised by about 72.5–130.3 K. The rate of heat increase on the lining decelerates as the online preheating was prolonged. As for the effect on the temperature drop of molten steel in heavy ladle process, 30 min of online preheating had almost the same effect as the full-process capping. Highlights: Unsteady numerical models for ladles with ladle lid or under regenerative baking were developed. The effect of different ladle capping processes or online preheating time on temperature drop of molten steel were analyzed. A 30 min of online preheating showed the same heat preserving effect as the full-process ladle capping.